2010
DOI: 10.2298/abs1003595p
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of viruses infecting the bean in Serbia

Abstract: This work describes the incidence and distribution of the most important bean viruses in Serbia: Bean common mosaic virus (BCMV), Bean common mosaic necrosis virus (BCMNV), Bean yellow mosaic virus (BYMV), Cucumber mosaic virus (CMV) and Alfalfa mosaic virus (AMV). The viral isolates were characterized serologically and biologically. BCMV was found in the largest number of plants (30.53%), followed by BCMNV (2.67%), CMV (5.34%), and AMV (3.41%), since BYMV was not determined. Mixed viral infections were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
1
9
1
5
Order By: Relevance
“…Similar results were obtained for field-grown pepper in Turkey with PVY and TMV in double infections [24], or with PVY and ToMV in Ethiopia [25], with PVY and CMV in Serbia [26], and in tomatoes in Valencia (Spain) where PVY and ToMV were the predominant viruses [5]. The inland climatic conditions of the Andalusian regions where these field pepper crops were located did not favor the presence of F. occidentalis thrips and the transmission of TSWV.…”
Section: Discussionsupporting
confidence: 72%
“…Similar results were obtained for field-grown pepper in Turkey with PVY and TMV in double infections [24], or with PVY and ToMV in Ethiopia [25], with PVY and CMV in Serbia [26], and in tomatoes in Valencia (Spain) where PVY and ToMV were the predominant viruses [5]. The inland climatic conditions of the Andalusian regions where these field pepper crops were located did not favor the presence of F. occidentalis thrips and the transmission of TSWV.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies reported that the incidences of BCMNV strains is lower than those of BCMV strains in most bean production areas of the world (Berger et al, 1997;Kostova et al, 2003;Petrović et al, 2010), but our two year survey in Urmia bean-producing regions indicated that BCMNV is prevalent in most regions.…”
Section: Resultscontrasting
confidence: 58%
“…Beberapa virus yang dilaporkan menyebabkan penyakit penting pada pertanaman kedelai ialah Soybean mosaic virus (SMV) (Andayanie 2012), Soybean stunt virus (SSV)/Cucumber mosaic virus galur soybean (CMV-S) (Asadi et al 2003), Cowpea mild mottle virus (CPMMV) (Akin 2003). Berdasarkan hasil penelitan Sulandari et al (2006) di rumah kaca, ditemukan juga bahwa Geminivirus dapat menginfeksi kedelai.…”
Section: Pendahuluanunclassified
“…Kedelai yang diinokulasi dengan BCMV menghasilkan gejala mosaik ringan yang tersebar di permukaan daun (Petrovic 2010). Berdasarkan gejala yang ditemukan di lapangan, sulit membedakan mosaik yang disebabkan CMV dan BCMV.…”
Section: Pembahasanunclassified
See 1 more Smart Citation